Field manipulation of electromagnetically induced transparency analogue in terahertz metamaterials for enhancing liquid sensing. (October 2022) - Lin, Tingling; Huang, Yi; Zhong, Shuncong; Zhong, Yujie; Zhang, Zhenghao; Zeng, Qiuming; Yu, Yingjie; Peng, Zhike
Highlights: A method of manipulating the electric field for enhancing liquid sensing is reported. The electric field tightly confined inside the structure by optimizing the fully-enclosed metamaterial structure design. The effective regional substrate etching realize maximumly light-matter interaction. The measurements reveal significantly improve in sensitivity of 0.312 THz/RIU, which is 9.8 times to that without etching by contrast. Abstract: Terahertz (THz) metamaterial sensing, an emerging technology in biomedical sciences, has made considerable progress with unique characteristics, such as label-free, non-invasive, non-destructive, and efficient. However, excellent sensing performance involves the need for extremely strong light-matter interaction that is difficult to implement for the intrinsic divergent electric field excited on the surface of metamaterials. Here, an innovative method of manipulating the electric field to realize maximumly light-matter interaction for enhancing liquid sensing at THz frequencies is reported. The electric field of electromagnetically induced transparency (EIT) resonance is tightly confined inside the structure around the quasi-dark mode by optimizing the fully-enclosed metamaterial structure design. More importantly, the electric field is enhanced and the part that permeates into the substrate is exploited, together with the formation of inartificial fluid loading units by the effective regional substrate etching, exhibiting the enhanced interaction between the polar liquids and the THz waves. The measurements reveal a significantly improve in sensitivity of 0.312 THz/RIU, which is 9.8 times that without etching by contrast. The strong light-matter interaction implements in THz metamaterial via the electric field manipulation holds bright promises for realizing highly sensitive THz sensing, forging a route for real-time supervising trace biomolecules. Graphical abstract: Image, graphical abstract